234k views
5 votes
Please help I need to finish my winter packet and no one is answering my questions

Please help I need to finish my winter packet and no one is answering my questions-example-1
User Akash D
by
5.3k points

1 Answer

5 votes

Answer:


\sqrt[7]{x^(4)}


(x^{(1)/(7)})^(4)


(\sqrt[7]{x})^(4)

Explanation:

we have


x^{(4)/(7)}

Remember the properties


\sqrt[n]{a^(m)}=a^{(m)/(n)}


(a^m)^(n)=a^(m*n)

so

Verify each case

Part 1) we have


\sqrt[4]{x^(7)}

we know that


\sqrt[4]{x^(7)}=x^{(7)/(4)}

Compare with the given expression


x^{(7)/(4)} \\eq x^{(4)/(7)}

Part 2) we have


\sqrt[7]{x^(4)}

we know that


\sqrt[7]{x^(4)}=x^{(4)/(7)}

Compare with the given expression


x^{(4)/(7)} = x^{(4)/(7)}

therefore

Is equivalent to the given expression

Part 3) we have


(x^{(1)/(7)})^(4)

we know that


(x^{(1)/(7)})^(4)=x^{(4)/(7)}

Compare with the given expression


x^{(4)/(7)} = x^{(4)/(7)}

therefore

Is equivalent to the given expression

Part 4) we have


(x^{(1)/(4)})^(7)

we know that


(x^{(1)/(4)})^(7)=x^{(7)/(4)}

Compare with the given expression


x^{(7)/(4)} \\eq x^{(4)/(7)}

Part 5) we have


(\sqrt[4]{x})^(7)

we know that


(\sqrt[4]{x})^(7)=(x^{(1)/(4)})^(7)=x^{(7)/(4)}

Compare with the given expression


x^{(7)/(4)} \\eq x^{(4)/(7)}

Part 6) we have


(\sqrt[7]{x})^(4)

we know that


(\sqrt[7]{x})^(4)=(x^{(1)/(7)})^(4)=x^{(4)/(7)}

Compare with the given expression


x^{(4)/(7)} = x^{(4)/(7)}

therefore

Is equivalent to the given expression

User Tiberiu Petcu
by
5.5k points